The Effect of ERP System Implementation in Improving Supply Chain Management Performance of Global Star Companies - Cindy Cindy; Helen Salwa; Selina Selina; Warna Gamelia; Warni Gamelia (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2023)
Global Star Company is a prominent player in the retail industry, operating in the bustling city of Batam. As part of its commitment to staying ahead in a highly competitive global market, the company has embraced the implementation of Enterprise Resource Planning (ERP) systems. This strategic move is geared towards enhancing various aspects of its operations, particularly in the supply chain. In today's globalized business landscape, it's imperative for companies like Global Star to optimize their supply chain processes. ERP systems facilitate the seamless integration of various functions, from material procurement and production to product delivery. The integration extends not only within the company but also externally, connecting with suppliers, distributors, and partners. This interconnectedness streamlines operations, reducing inefficiencies, and ensuring a more responsive supply chain. One critical element of Global Star's ERP infrastructure is the GF Accounting software, a versatile and multifunctional tool that plays a pivotal role in managing the company's financial operations. This software is not limited to just supermarkets but is also used across various industries to maintain control over business activities and accurately record transactions. By doing so, it empowers the company to gain better insights into its financial health and performance. Global Star recognizes that its success depends on more than just offering a wide range of products. It hinges on the efficiency and effectiveness of its internal and external business processes. The ERP system, combined with the GF Accounting software, is a driving force behind the company's ongoing efforts to streamline these processes, reduce costs, and enhance overall performance. In conclusion, Global Star Company's adoption of ERP systems and the GF Accounting software underscores its commitment to staying competitive in the global retail industry. By leveraging technology to improve supply chain management and optimize financial operations, the company is poised for continued growth and success in the dynamic and challenging world of retail.